Novel variants in POLH and TREM2 genes associated with a complex phenotype of xeroderma pigmentosum variant type and early‐onset dementia. Issue 11 (16th September 2020) - Soares, Izadora Fonseca Zaiden; Christofolini, Denise Maria; Silva, Lis Gomes; Feder, David; de Siqueira Carvalho, Alzira Alves
Abstract: Background: Xeroderma pigmentosum (XP) is a rare, genetically heterogeneous, autosomal recessive disorder caused by defects in the genes involved in repairing DNA damaged by ultraviolet radiation. These defects lead to a propensity to develop skin cancer at early ages as a hallmark, and progressive neurological degeneration can be observed in around 25% of patients. Eight clinically heterogeneous groups have been identified so far (XPA to XPG and XPV). Xeroderma pigmentosum variant type (XPV) is associated with pathogenic variants in POLH on chromosome 6, and no neurological dysfunction has been seen in these cases. However, on the same chromosome, it has been shown that TREM2 is associated with some types of dementia, particularly in patients with a behavioral variant frontotemporal phenotype. Methods: Gene mutational analysis was performed by whole‐exome sequencing. Results: We report a case of a Caucasian woman with XP that developed behavioral and cognitive impairment at age 37. Whole‐exome sequencing identified novel homozygous variants in POLH c.638C>G (p.Ser213*) and TREM2 c.154C>T (p.Arg52Cys), classifying the patient as XPV and suggesting that her frontotemporal dementia phenotype could be related to the variant in TREM2 . Conclusion: This paper describes a rare case of a patient with two novel variants in the same chromosome associated with XPV and early‐onset dementia. Abstract : We report a case of a patient with xeroderma pigmentosum variant type who developed early‐onset dementia, in which two novel gene variants in POLH and TREM2 were found.